Design and analysis of fuel cell stack for automotive use - Mohiuddin, A. K. M.; Syafie, Ahmad; Khan, Ahsan Ali (Praise Worthy Prize, 2018)
Fuel cell is one of the promising power generators that can convert chemical energy in the reactants (hydrogen and oxygen) into useful electrical current, water and heat. It can be used as a power plant to power vehicles propulsion system. This technology is new to the automotive industries in Malaysia, where the default engines used in vehicles are internal combustion engines (ICE). This paper describes the fundamentals of the operating principle for various types of fuel cells, the suitable type of fuel cell to be used in an automotive propulsion system, the design of fuel cell stack, and the calculation to find the power output from fuel cell stack. The proposed design of the selected fuel cell stack (Proton Exchange Membrane Fuel Cell, PEMFC) is designed by using computer aided design (CAD) software which is SOLIDWORKS; instead, ANSYS FLUENT is used to simulate and analyze the optimal temperature and pressure by relying on the simple fuel cell stack (Single Turn Serpentine PEMFC). Based on the simulation, it is found that the optimal operating temperature and pressure are 323 K and 3.5 atm respectively. The result obtained is plotted in a graph for a better understanding; observation and required discussion of the result are provided. Also, an experiment has been conducted to obtain efficiency of Reversible PEMFC, and a simulation by ANSYS FLUENT has been provided. It has been found that the efficiency based on both the simulation and the experimentation is 58.85 % and 56.25 % respectively. Then, the percentage error calculated between these two results in term of energy output is found to be 3.83%.